Analysis of the influence of groove welds of oxy-acetylene welding joints on tensile strength and microstructure on steel ST 37 - Nugroho, Fajar; Muga, Yohanes Fernando Leo; Setiabudi, Dedet Hermawan; Sudarmanto, Sudarmanto (Institut Teknologi Dirgantara Adisutjipto, 2024)
In this study, the authors conducted a study on the analysis of the effect of oxy-acetylene welding joints on tensile strength and microstructure in the HAZ and weld metal areas on st 37 steel plates. The results of this study indicate that the average value of the highest tensile strength value is at V groove weld with the average strength of the welded joint is 4.796 kgf/mm2. While the lowest tensile stress is on the I groove weld of 4.674 kgf/mm2. Meanwhile, from the microstructure test, it can be seen that in the HAZ area each groove. Microstructure in the HAZ area shows that the double V groove weld types are fine ferrite, coarse pearlite and martensite. In type V groove weld the structures formed are ferrite, coarse pearlite and martensite. In type I groove weld the structures formed are ferrite, grain boundary ferrite and fine pearlite. Whereas in the weld metal area, and the results of the microstructure test of the weld area on the V seam, it shows a dense microstructure arrangement, the arrangement is identical to pearlite (dark color) so that the specimen is harder.